The Specifics of Supply Chain Integration with Small and Medium-Sized Enterprises - Logožar, Klavdij (Naše gospodarstvo/Our economy, 2013)
Although larger organizations have invested significant amounts of money to integrate their supply chains, the development of supply chain integration with small and medium-sized enterprises (SMEs) is slow-moving. For SMEs, integration is a significant problem due to high costs and technology requirements. Hence, they fol- low a different approach to integrate their supply chains. Full integration of supply chains from the procurement of raw material to the distribution of finished goods is considered to be a crucial issue as nowadays the competition among enterprises is about supply chain efficiency, which is based on tighter cooperation of all partners in the supply chain process. This paper attempts to explore this topic by exploring how SMEs integrate their supply chains and by identifying the benefits of integrat- ing supply chains.
Keywords: supply chain; integration; SMEs; e-business